Peran Tata Usaha Dalam Meningkatkan Kualitas Pelayanan Administrasi di MTs Nurul Fajri Desa Tambangan Kelekar - Saipul Annur; Nyayu Khodijah; Amilda Amilda; Ibrahim Ibrahim; Ika Leilani; Hidayat Hidayat; Nurviana Nurviana (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2021)
This aarticle is motivated by how the role of administration in improving the quality of administrative services at MTS Nurul Fajri Tambangan Kelekar Village, the role of administration in improving administrative services there are 3 main points, namely: 1) Serving the implementation of operative work to achieve the goals of an organization 2) Providing information -information for the superiors of the leadership of the Organization so that they can make decisions or take appropriate actions 3) Assisting the smooth development of the organization as a whole. As for administrative services, namely an effort provided by the school to students to be more optimal and all joint efforts to utilize resources, both personal and material, effectively and efficiently in order to optimally support the achievement of goals. This study aims to determine the role of administration in improving the quality of administrative services at MTS Nurul Fajri. This type of research is qualitative research using descriptive methods. In this study, this study used several data collection techniques, including interview techniques, observation techniques and documentation studies. The results of the study show that the role of administration in improving the quality of administrative services at MTS Nurul Fajri that administrative staff plays an active role in improving the quality of administrative services at MTS Nurul Fajri Tambangan Kelekar Village, but because there are still many things that need to be learned so that developments in its administrative services developed gradually.